(untitled) (Research, Society and Development, 2020)
Pepper fruit oil has antioxidant and antifungal properties that can benefit the health and well-being of fish. The objective of this study was to evaluate the benefits of the inclusion of brazillian pepper crude oil in the development and staining of Mato Grosso fish (Hyphessobrycon eques Steindachner, 1882). A total of 68 specimens of bush were distributed in four 10 L units in an individual recirculation system and thermostat water at 28° C. During the 60-day test, the fish were fed commercial diet (DC) and commercial diet supplemented with brazillian pepper essential oil (5g.kg-1) (DP). At the end of the experimental period, survival, growth, staining and thermogenicity were evaluated. Data were analyzed by the Tukey test (P>0.05). The addition of brazzilian pepper oil promoted higher fish survival (94.11%) and better condition factor (1.87). There was no difference in diet consumption by fish. However, the growth factors were smaller compared to the control group, except for the gain in length. The control group presented more homogenous weight, while the best size uniformity was obtained for the DP group. In highlight the DP provided an increase in fish thermogenicity and also increased staining in the L* and a* indices. It is concluded that this dose of pink pepper oil is not recommended as a complement to optimize color in ornamental fish, however, the substance is shown as a promising bioactive for the development of the immune system of these fish.